Making a Video Profile of the Sultan Mahmud Riayat Syah Mosque - Ananda Roy; Ahmad Hamim Thohari (Politeknik Negeri Batam, 2020)
In making mosque profile videos, the author chooses to use video to make it more interesting to see both in the community and for a wider scope such as introducing the media as religious tourism. Methods for using data using observation and literature study. After obtaining data to solve existing problems, namely using SWOT analysis (strengths, weaknesses, opportunities, threats) in order to position which ones need attention in the mosque profile video and be different from other mosques. In making a video profile of the Sultan Mahmud Riayat Syah Mosque, the author uses the Luther Sutopo method. There are 6 (six) stages of the development method, namely concept, design, material collection, assembly, testing and distribution. The research that resulted from the making of video profiles was analyzed from the quality of the video which was measured from the material and media aspects using the Likert scale and got